Practical Approach to the Diagnosis of the Vulvo-Vaginal Stromal Tumors: An Overview - Giuseppe Angelico; Stefano Marletta; Giuseppe Broggi; Paolo Vigneri; Giada Maria Vecchio; Lucia Salvatorelli; Gaetano Magro (Diagnostics, 2022)
Background: The category of the “stromal tumors of the lower female genital tract” encompasses a wide spectrum of lesions with variable heterogeneity, which can be nosologically classified on the basis of their morphologic and immunohistochemical profiles as deep (aggressive) angiomyxoma (DAM), cellular angiofibroma (CAF), angiomyofibroblastoma (AMFB) or myofibroblastoma (MFB). Despite the differential diagnosis between these entities being usually straightforward, their increasingly recognized unusual morphological variants, along with the overlapping morphological and immunohistochemical features among these tumours, may raise serious differential diagnostic problems. Methods and Results: The data presented in the present paper have been retrieved from the entire published literature on the PubMed website about DAM, CAF, AFMB and MFB from 1984 to 2021. The selected articles are mainly represented by small-series, and, more rarely, single-case reports with unusual clinicopathologic features. The present review focuses on the diagnostic clues of the stromal tumours of the lower female genital tract to achieve a correct classification. The main clinicopathologic features of each single entity, emphasizing their differential diagnostic clues, are discussed and summarized in tables. Representative illustrations, including the unusual morphological variants, of each single tumour are also provided. Conclusion: Awareness by pathologists of the wide morphological and immunohistochemical spectrum exhibited by these tumours is crucial to achieve correct diagnoses and to avoid confusion with reactive conditions or other benign or malignant entities.